Antifungal activity of volatile and non-volatile metabolites of endophytes of Chloranthus elatior Sw. - Santra, Hiran Kanti; Banerjee, Debdulal (Frontiers in Plant Science, 2023)
Fungal infections in agricultural crops cause huge economic losses and hamper overall crop productivity. The application of chemical fungicides to combat the situation leads to further detrimental side effects. There is an urgent need for safe and novel antifungals. Volatiles from plant-beneficial endophytic fungi is considered promising alternatives to be used in the biological control of fungal pathogens, as a sustainable approach in an agroecosystem. In the present investigation, a volatile emitting sterile endophytic fungus Diaporthe sp. CEL3 with bio-fumigation activity was isolated from leaves of the ethnomedicinal plant Chloranthus elatior Sw., collected from the Passighat forest of North-East India. Camphor odor volatiles of CEL3 showed an inhibitory effect against eight fungal pathogens in vitro and minimised the infections of Monilinia fructicola, a causal agent of fruit rot of cherry, in VOC-exposed cherry fruits. Rhizoctonia solani, Botrytis cinerea, Pythium ultimum, M. fructicola were maximally inhibited upto 51.5%, 55.8%, 61.9%, and 78.5% respectively in comparison to control by the volatiles. Another isolate CEL7 identified as Curvularia sp. synthesised non-volatile soluble antifungal metabolites in its cell-free extracts and exhibited antifungal action. Bioassay-guided fractionation revealed the presence of imidazole compounds- (2-aminoethyl)-1H-imidazole-2-carbaldehyde, Pyrazole 4, 5 imidazole, 1-formyl 3 ethyl, phenol compounds- Phenol, 4-[2-(methylamino) ethyl]-, 6-Nitro-3-chlorophenol, Phenol, 2,4,6-tri-tert-butyl- etc. in the cell-free extracts with a MIC value of 250-2000 µg mL-1. Optimum VOC emission was achieved in a modified PDA media with instantly smashed potato (150 g L-1), dextrose (20 g L-1), wheat husk (20 g L-1), and yeast extract (20 g L-1), with additional salts. Interestingly endophytic CEL3 emitted different types of volatiles and Trans-verbenol (32.25%), Geraniol (30.32%), Trans-ocimenol (12.90%), Mentha-4,8-diene (5.16%) were the prime ones. These VOCs cause lethal leakage of protein and necessary intracellular molecules from the fungal pathogens. Thus, CEL3 could potentially be used as a bio-fumigating agent to control post-harvest infections caused by fungal pathogens. This study opens up a new approach to the use of endophytic fungi in biocontrol.